The Relevance of Al-Syaibany’s Thought to the Integrated Islamic School’s Integrative Curriculum: A Case Study at SMAIT Fithrah Insani - Jauhar Jundi Azkia; Syahidin Syahidin; Jenuri Jenuri (Jurnal Penelitian Medan Agama, 2026)
Studies on integrative curricula in Integrated Islamic Schools have generally been dominated by research at the primary education level and literature reviews, leaving a gap in empirical analysis based on classical philosophy at the Senior High School (SMA) level. This qualitative research employing a case study method aims to evaluate the relevance of Omar Mohammad Al-Toumy Al-Syaibany’s curriculum thought at SMAIT Fithrah Insani in addressing the dichotomy between religious and general sciences. The results conclude that Al-Syaibany’s classical philosophical ideas are adaptively and vividly reflected in three main pillars: the normative aspect, which positions tawhid as an overarching worldview through cross-disciplinary assignments and structured daily religious habituation; the humanistic aspect, which recognizes students' multidimensional fitrah through holistic evaluation and academic writing autonomy; and the systemic aspect, which demonstrates a dynamic and flexible stance in responding to curriculum transitions. The primary contribution of this study provides empirical evidence that Al-Syaibany’s classical philosophy can be realistically and adaptively implemented in modern schools to address contemporary challenges. This research also enriches Islamic education curriculum studies, serves as a guideline for teachers in integrating knowledge, and offers insights for policymakers.